Kontribusi Pemahaman Hadis tentang Larangan Qaza’ dan Implementasinya di Desa Dolok Hataran Kecamatan Siantar Kabupaten Simalungun - Ridho, Muhammad Taufik; Sulidar, Sulidar (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This research is based on the phenomenon of the practice of qazaʻ, namely shaving part of the head and leaving the rest, which is still found in Dolok Hataran Village, Siantar District, Simalungun Regency. This practice contradicts the prohibition conveyed in the Prophet’s hadith because it is considered similar to the tradition of ignorance, contains elements of imperfection in appearance, and has the potential to cause social stigma. The purpose of this study is to analyze the public’s understanding of the hadith prohibiting qazaʻ and examine the implementation of the hadith’s values in everyday life. The method used is qualitative with a phenomenological approach through interviews, observation, and documentation. The results show that the public’s understanding of qaza' is still limited to the physical dimension of shaving hair without considering the normative basis of the hadith. Some people consider qazaʻ only a children’s hairstyle, while a handful of religious leaders emphasize the prohibition as part of Islamic ethics in maintaining self-respect. The implementation of the hadith in the field is not consistent; despite counseling from religious leaders, qazaʻ is still found at certain moments such as traditional parties or the style of modernization of youth. The implications of these findings indicate the importance of strengthening hadith literacy in religious education and more communicative cultural daʻwah, so that the values contained in the hadith regarding the prohibition of qazaʻ are not only understood normatively but can also be internalized in social behavior, forming collective awareness, and encouraging the transformation of local traditions towards religious practices that are in line with Islamic teachings.